Clinical trial demonstrates exercise following bariatric surgery improves insulin sensitivity - Coen, Paul M. (J Clin Invest, 2014)
BACKGROUND. Roux-en-Y gastric bypass (RYGB) surgery causes profound weight loss and improves insulin sensitivity (S(I)) in obese patients. Regular exercise can also improve S(I) in obese individuals; however, it is unknown whether exercise and RYGB surgery–induced weight loss would additively improve S(I) and other cardiometabolic factors. METHODS. We conducted a single-blind, prospective, randomized trial with 128 men and women who recently underwent RYGB surgery (within 1–3 months). Participants were randomized to either a 6-month semi-supervised moderate exercise protocol (EX, n = 66) or a health education control (CON; n = 62) intervention. Main outcomes measured included S(I) and glucose effectiveness (S(G)), which were determined from an intravenous glucose tolerance test and minimal modeling. Secondary outcomes measured were cardiorespiratory fitness (VO(2) peak) and body composition. Data were analyzed using an intention-to-treat (ITT) and per-protocol (PP) approach to assess the efficacy of the exercise intervention (>120 min of exercise/week). RESULTS. 119 (93%) participants completed the interventions, 95% for CON and 91% for EX. There was a significant decrease in body weight and fat mass for both groups (P < 0.001 for time effect). S(I) improved in both groups following the intervention (ITT: CON vs. EX; +1.64 vs. +2.24 min(–1)/μU/ml, P = 0.18 for Δ, P < 0.001 for time effect). A PP analysis revealed that exercise produced an additive S(I) improvement (PP: CON vs. EX; +1.57 vs. +2.69 min(–1)/μU/ml, P = 0.019) above that of surgery. Exercise also improved S(G) (ITT: CON vs. EX; +0.0023 vs. +0.0063 min(–1), P = 0.009) compared with the CON group. Exercise improved cardiorespiratory fitness (VO(2) peak) compared with the CON group. CONCLUSION. Moderate exercise following RYGB surgery provides additional improvements in S(I), S(G), and cardiorespiratory fitness compared with a sedentary lifestyle during similar weight loss. TRIAL REGISTRATION. clinicaltrials.gov identifier: NCT00692367. FUNDING. This study was funded by the NIH/National Institute of Diabetes and Digestive and Kidney Diseases (R01 DK078192) and an NIH/National Center for Research Resources/Clinical and Translational Science Award (UL1 RR024153).